The Mann-Whitney U: A Test for Assessing Whether Two Independent Samples Come from the Same Distribution - Nachar, Nadim (Tutorials in quantitative methods for psychology, 2008)
It is often difficult, particularly when conducting research in psychology, to have access to large normally distributed samples. Fortunately, there are statistical tests to compare two independent groups that do not require large normally distributed samples. The Mann-Whitney U is one of these tests. In the following work, a summary of this test is presented. The explanation of the logic underlying this test and its application are presented. Moreover, the forces and weaknesses of the Mann-Whitney U are mentioned. One major limit of the Mann-Whitney U is that the type I error or alpha (?) is amplified in a situation of heteroscedasticity.